2022
DOI: 10.1063/5.0082671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blade tip cutting angle on energy conversion mechanism of side channel pumps

Abstract: Typical industrial blade side channel pumps with tip cuts have been used for many years because the blade profile has significant effect on the performance of the pump. To investigate the effect of the tip cutting angle on the energy conversion mechanism of the pump, the original and the industrial blades with different tip cutting angles were studied in detail. A comprehensive analysis revealed that the cutting tip enhances the hydraulic performance of the side channel pump, especially when the angle is equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As can be seen from the figure 10, when the flow rate is 160L/h, the efficiency of model #2.2, model #2.4 and model #2.5 is higher than that of model #2.3, and the efficient working region will not only shift towards large flow, but also towards small flow. From the above analysis, it is concluded that the impeller height has two effects on the performance of RFP: (1) In order to ensure high head and high efficiency of RFP at rated flow rate, there is an optimal value of impeller height. ( 2) As the height of the impeller is greater than the optimal value, the head of the RFP will gradually be the same, and the efficiency curve turn to be much slower.…”
Section: Performance Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from the figure 10, when the flow rate is 160L/h, the efficiency of model #2.2, model #2.4 and model #2.5 is higher than that of model #2.3, and the efficient working region will not only shift towards large flow, but also towards small flow. From the above analysis, it is concluded that the impeller height has two effects on the performance of RFP: (1) In order to ensure high head and high efficiency of RFP at rated flow rate, there is an optimal value of impeller height. ( 2) As the height of the impeller is greater than the optimal value, the head of the RFP will gradually be the same, and the efficiency curve turn to be much slower.…”
Section: Performance Curvesmentioning
confidence: 99%
“…In recent years, relevant scholars have carried out a series of theoretical, experimental and numerical simulation studies on the structure improvement of blade and flow channel, unsteady flow inside RFP, and cavitation of RFP. Chen et al [1] investigated the impact of tip cutting angle on the energy exchange mechanism of a side channel pump, and discovered that utilizing the proper tip cutting angle structure can enhance the hydraulic performance of the pump. Notably, a tip cutting angle of 20° was found to significantly improve pump efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et. Al [11] applied Galilean Invariance in analyzing vortices in a side channel pump, and they presented the influence of radial vortices and axial vortices.…”
Section: Introductionmentioning
confidence: 99%